Application of NASA-TLX and SHERPA in Setting Up Fused Filament Fabrication Equipment (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 2019)
The use of new technologies in productive processes nowadays poses a challenge to the users, mainly because those technologies create them a necessity for learning and adaptation. This study focused on the assessment and analysis of mental workload and human error as experienced by users of Fused Filament Fabrication (FFF) printers, which is the most recent development in a series of technologies known as Additive Manufacturing (AM). Eight subjects were asked to complete the setting up of three commercial FFF equipment. Hierarchical Task Analysis (HTA) was used to describe the tasks. NASA-TLX method was used to assess the mental workload involved, and SHERPA method was applied to identify human errors while completing the task. The results of HTA show that leveling the printing bed is the most demanding activity on the subject's concentration. NASA-TLX shows that Mental Demand subscale had the highest average punctuation with 78.75 points, followed by Temporal Demand with an average of 61 points. As for SHERPA analysis, 59 human errors were identified in that particular task. In detail, 54.2% were action errors, 22.0% were selection errors, and 18.6% were checking errors. The combination of HTA, NASA-TLX and SHERPA techniques, permitted a complete analysis of the interaction between humans and this technology, opening the way to improvements in the design of FFT equipment which possibly might prevent future effects on user’s health.